2003
DOI: 10.1177/0269881103174018
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Hyperforin Content of Hypericum Perforatum(St John’s Wort) Extracts with Their Effects On Alcohol Drinking in C57Bl/6J Mice: A Preliminary Study

Abstract: Extracts of the herb St John's Wort have been shown to reduce alcohol intake in alcohol-preferring rats, but it is not known which of the constituent(s) are responsible for this effect. In this study, the effect of a crude methanolic extract of Hypericum perforatum (negligible hyperforin content) on alcohol drinking in C57BL/6J alcohol-preferring mice was compared with that of a hyperforin-rich extract (45% hyperforin) prepared by extracting the herb with supercritical carbon dioxide. The dose of the hyperfori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Animal studies suggest that acute administration of hypericum can reduce voluntary alcohol intake and act synergistically with opiate antagonists [8 ]. Two recent studies examining the effects of hypericum on alcohol intake in rats confirm previous research and demonstrate that the constituent hyperforin contributes to observed reduction in alcohol intake [15,16]. Hyperforin is currently considered to be the primary contributor to antidepressant effects [17].…”
Section: Reducing Hazardous Alcohol Intakementioning
confidence: 56%
“…Animal studies suggest that acute administration of hypericum can reduce voluntary alcohol intake and act synergistically with opiate antagonists [8 ]. Two recent studies examining the effects of hypericum on alcohol intake in rats confirm previous research and demonstrate that the constituent hyperforin contributes to observed reduction in alcohol intake [15,16]. Hyperforin is currently considered to be the primary contributor to antidepressant effects [17].…”
Section: Reducing Hazardous Alcohol Intakementioning
confidence: 56%
“…All of them were performed on experimental animals. It has been suggested that HPE inhibits ethanol intake and preference in several strains of ethanol preferring rats (Rezvani et al, 1999;De Vry et al, 1999;Perfumi et al, 1999Perfumi et al, , 2001Perfumi et al, , 2002 and mice (Wright et al, 2003). In a recent report, Perfumi et al (2005) showed that HPE significantly reduced ethanol self-administration, while it did not modify saccharin self-administration.…”
Section: Hpe and Ethanol Dependencementioning
confidence: 99%
“…It was concluded that these multidimensional effects of St. John’s wort were most likely the consequence of two separate actions rather than to a single related mechanism. The chemical that is responsible for the actions of St. John’s wort has not yet been confirmed, but some evidence points to hyperforin (Wright et al . 2003; Perfumi et al .…”
Section: Conclusion/further Directionsmentioning
confidence: 99%